RECURRENT ANCA-ASSOCIATED VASCULITIS AFTER KIDNEY ALLOTRANSPLANTATION - N. F. Frolova; L. Yu. Artyukhina; E. S. Stolyarevich (Научно-практическая ревматология)
The paper describes a clinical case of recurrent microscopic polyangiitis diagnosed 10 years after kidney allotransplantation that was accompanied by the hyperproduction of antibodies to myeloperoxidase, graft damage with the morphological picture of pauci-immune extracapillary glomerulonephritis with crescents and other systemic manifestations, including interstitial lung injury complicated by hemoptysis. An effect is produced by biological anti-B-cell therapy with rituximab. The discussion involves the detailed review of the literature.